2001
DOI: 10.1039/b007303m
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of allethrin, deltamethrin, esbiothrin, prallethrin and transfluthrin in air during the use of household mosquito repellents

Abstract: Three types of mosquito repellent [two different mosquito coils containing allethrin 0.1% w/w and transfluthrin 0.03% w/w, an aerosol sample containing a combination of two pyrethroid molecules (deltamethrin 0.02% w/w + allethrin 0.13% w/w) and two different mosquito mats containing esbiothrin 2.0% w/w and prallethrin 1.5% w/w as active ingredients] were individually subjected to use in a closed room. Air samples from the room were drawn at different time intervals (15, 30 and 45 min, and 1, 2, 4, 6 and 8 h) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 11 publications
0
17
2
1
Order By: Relevance
“…In the case of the aerosol spray, indoor air concentrations of active ingredient pyrethroids in the current study were much lower than those reported in other studies (Class and Kintrup, 1991;Ramesh and Vijayalakshmi, 2001). The differences in the amount of spray being used and sampling duration after the spray were the likely reasons for the variation in pyrethroid concentrations reported among studies.…”
Section: Occurrence Of Pyrethroids In Indoor Air During Mr Applicationscontrasting
confidence: 89%
See 1 more Smart Citation
“…In the case of the aerosol spray, indoor air concentrations of active ingredient pyrethroids in the current study were much lower than those reported in other studies (Class and Kintrup, 1991;Ramesh and Vijayalakshmi, 2001). The differences in the amount of spray being used and sampling duration after the spray were the likely reasons for the variation in pyrethroid concentrations reported among studies.…”
Section: Occurrence Of Pyrethroids In Indoor Air During Mr Applicationscontrasting
confidence: 89%
“…and Kintrup, 1991;Nazimek et al, 2011;Vesin et al, 2013), but were orders of magnitude lower than the concentrations reported by Ramesh and Vijayalakshmi (2001). In the case of the aerosol spray, indoor air concentrations of active ingredient pyrethroids in the current study were much lower than those reported in other studies (Class and Kintrup, 1991;Ramesh and Vijayalakshmi, 2001).…”
Section: Occurrence Of Pyrethroids In Indoor Air During Mr Applicationscontrasting
confidence: 62%
“…Due to the analytical constraints and to the low background levels of pesticides found indoor that require extended time of accumulation, the sampling time typically ranged from more than 1 h up to several days [50][51][52]. Leva et al [47], Berger-Preiss et al [48], and Ramesh and Vijayalakshmi [53] managed to reduce it to <1 h, but for a relatively limited number of measures. In contrast, the measurement frequency drops to one measurement per minute or less with the HS-PTR-MS, potentially for extended periods of measurement time (24 h or more).…”
Section: Field Measurementsmentioning
confidence: 99%
“…Pesquisas direcionadas ao entendimento do destino ambiental dessas substâncias e dos efeitos adversos causados a organismos não alvos, como seres humanos, animais e meio ambiente em geral, têm sido intensificadas. Diversos estudos têm evidenciado a ocorrência de resíduos de pesticidas em produtos alimentícios [1][2][3][4][5][6][7][8][9] e no meio ambiente, [10][11][12][13][14][15][16][17][18] especialmente na água. Considerando as dimensões do território brasileiro e o elevado consumo de pesticidas, o número de publicações apresentando resultados indicativos da presença destes compostos em água superficial [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] e subterrânea, 22,26,31,32,34,36,[38][39][40]…”
Section: Introductionunclassified